GeneXpert as diagnostic method of tuberculosis in Santiago de Cuba - Dainer Rogelio Acosta Sánchez; Leordanys Domínguez Sánchez; Joaquín López González; Serguei Duarte Grandales (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: Tuberculosis is a health problem worldwide, reason why methods as the GeneXpert are needed to carry out a quick and safe diagnosis. Objective: To determine the accuracy of GeneXpert as a method for the diagnosis of tuberculosis in Santiago de Cuba in connection with the traditional studies. Methods: A descriptive and cross-sectional study was carried out from December, 2018 to the same month in 2019 of 31 patients to whom the 3 methods for the diagnosis of tuberculosis were carried out. Some variables were used, such as age, sex, studied samples, positivity of the used methods, as well as consistency between the GeneXpert and the culture by means of the Kappa index. Results: In the series there was a prevalence of the patients over 50 years (48.4 %), male sex (66.7 %) and sputum as more representative sample (80.6 %); also, the culture was positive in 32.3 % and GeneXpert in 22.6 %. As long as, tuberculosis was diagnosed in 11 patients and the Kappa index was 0.58. Conclusions: The determination of GeneXpert in the diagnosis of tuberculosis is necessary, given its high sensibility and specificity in connection with the traditional studies of sputum and culture, which was confirmed due to the high consistency of the Kappa index.